DIMENSI KEJENIUSAN MAJIDAH DALAM NOVEL “AL-MAJIDAH ZIKRAYATU BILA ḤIBRIN WA WARAQIN” PERSPEKTIF LE GÉNIE FÉMININE JULIA KRISTEVA - Rabiatul Adawiyah Madawat M; Arni Mujahidah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
The novel Al-Majidah Zikrayatu Bila Hibrin Wa Waraqin by Abdullah al-Bargutsyi tells the story of a Palestinian woman named Majidah. Majidah was strictly prohibited from continuing her education due to the perception that women are not competent. Eventually, she was forced to marry an Israeli resistance nurse. It relates to one of the facts in Arab countries itself about claims against women who are considered less intelligent and eminent than men. Therefore, the aim of this research is to see how Majidah struggled in her life in voicing this injustice. Kristeva characterizes the struggles of Majidah's life as a dimension of female genius The methode employed in this research is qualitative escriptive. The material object is the Novel Al-Majidah Zikrayatu Bila Hibrin Wa Waraqin. The data source consist of text that are primary data, comparising, dialogues, descriptions, or actions in the novel regarding the characteristics of women’s genius. Therefore, the research is accordance with the thinking of Julia Kristeva's theory is Le Génie Féminin as the formal object which explores the genius traits in women through l’action and la vie. Kristeva revealed that female genius is not on the boundaries of the profession. As a result, this study reveals Majidah's genius fom the complexity of her life. She broke the social constructs by utilizing her abilities as a fighter and journalist. Every aspect of Majidah's being and actions exemplifies what Kristeva refers to as the genius of women. The significance of genius here moves more to action, life, and thought.